Flavian poetry and its Greek past - Augoustakis, Antony. (Mnemosyne, Supplements, 2014)
Flavian Poetry and its Greek Past breaks new ground by investigating the close interaction between Flavian poetry and Greek literary tradition and by evaluating the meaning of this affiliation in the socio-political and cultural context of the late first century CE. Authors examined include Martial, Silius Italicus, Statius, and Valerius Flaccus. Their interaction with Greek literature is not just thematic or geographical: the Greek literary past is conceived as the poetic influence of a variety of authors, periods, and genres, such as Homer, the Cyclic tradition, Greek lyric poetry, Greek tragedy, Hellenistic poetry and aesthetics, and Greek historiography.